2020
DOI: 10.1002/bab.1922
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sphk1/S1P and microRNAs in human cancers

Abstract: Sphingosine kinases type 1 (SphK1) is a key enzyme in the phosphorylation of sphingosine to sphingosine 1‐phosphate (S1P). Different abnormalities in SphK1 functions may correspond with poor prognosis in various cancers. Additionally, upregulated SphK1/S1P could promote cancer cell proliferation, angiogenesis, mobility, invasion, and metastasis. MicroRNAs as conserved small noncoding RNAs play major roles in cancer initiation, progression, metastasis, etc. Their posttranscriptionally mechanisms could affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…As a widely occurring secondary messenger molecule, S1P is a vital regulator of various diseases, including cancer, atherosclerosis, fibrosis, and multiple sclerosis [ 29–31 ]. Szasz et al [ 32 ] have demonstrated that overexpression of SphK1 predicts poor overall survival [ 33 ]. However, the putative association between miR-124a and the Sphk1/S1P pathway needs to be comprehensively elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…As a widely occurring secondary messenger molecule, S1P is a vital regulator of various diseases, including cancer, atherosclerosis, fibrosis, and multiple sclerosis [ 29–31 ]. Szasz et al [ 32 ] have demonstrated that overexpression of SphK1 predicts poor overall survival [ 33 ]. However, the putative association between miR-124a and the Sphk1/S1P pathway needs to be comprehensively elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Sphk1 can induce T cell failure through excessive S1P in extracellular vesicles of the tumor microenvironment. The study demonstrate that down regulation S1P lead to the increase of CD8 + T cells and decrease of Treg cells in the tumor microenvironment [6,7] . S1P also upregulates the expression of PD-L1 through Early 2 factor transcription factor 1 (E2F1) [8] .…”
Section: Introductionmentioning
confidence: 72%
“…Sphk1 catalyzes the phosphorylates of sphingosine to generate sphingosine-1-phosphate (S1P). Sphk1/S1P signal pathway not only influences tumor cells growth, proliferation, survival and angiogenesis, but also regulates immunotherapy [5,6] . Sphk1 can induce T cell failure through excessive S1P in extracellular vesicles of the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…These post-transcriptional gene regulators open a new field of research regarding the therapeutic role of CrM supplementation on health-related conditions. It needs to be noted that the osmosensing activation of MAPK via Sphk1/S1P is related to several miRNAs [ 142 ], as well as the notion that the effect of Cr on focal adhesion kinase [ 38 , 70 ] ( Figure A1 ) might control muscle cell differentiation through a small set of miRNAs that are connected to the focal adhesion signaling during muscle regeneration, as was reported recently [ 143 ]. Further experimental validation is warranted in the future.…”
Section: Discussionmentioning
confidence: 93%